A Rapid Assessment of Alpha Diversity by Use of Shannon Diversity Index-A Statistical Tool (International Journal of Scientific Research in Science and Technology, 2025)
The Shannon index is an information statistic index, which means it assumes all species are represented in a sample and that they are randomly sampled. Species richness, evenness, and diversity are used to compare different populations(Magurran, A. E. 2004.). This index quantifies the diversity of a community by considering both the number of species (species richness) and the evenness of their distribution(Species richness).Biodiversity indices can help prioritize conservation efforts by identifying areas of high biodiversity importance and species in need of protection(Simpson E.H. 1949) .They can also be used to assess the effectiveness of conservation and restoration projects, such as habitat restoration or invasive species management. In the present study Shannon-Weiner Species Diversity Index (H) was used to calculate biodiversity for site 1 and for site 2 in University Campus Kota Rajasthan India.Higher the value of H in site 1, indicated higher the diversity of tree species in that area .